Persuasive Language of Advertisement in People Magazine: A Semantic Study - Imelia Azzahra; Heri Heryono (Jurnal Sinestesia, 2023)
This research analyzes the persuasive language used in magazine advertisements, namely People Magazine. The research purpose is to discover types of persuasive techniques and recognize the deeper meaning of the persuasive sentences used in People Magazine. The theory of Lamb (2019) is used as the main theory to support conducted this research. The qualitative method is also applied to this research. The object of this research was the article advertisement posted in People Magazine, starting from the headline, picture caption, and content. After analyzing the data, the writer found 12 persuasive techniques out of 25 techniques of Lamb's theory used in People Magazine. From 30 ads, found 12 types of techniques and it can be classified as follow: 6 data of hyperbole, 4 data of evidence, 3 data of simile, 3 data of emotive,1 data of imagery, 2 data of colloquial language, 1 data of rhetorical questions, 2 data of expert opinion, 3 data of assonance, 1 data of tradition, 3 data of connotation, and 1 data of inclusive language. People Magazine dominantly used Hyperbole techniques on their advertisement. It shows that People Magazine itself wants to posted an advertisement article that can grab reader’s attention, make their message notable and underline product qualities.